2016
DOI: 10.1515/cdbme-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage conditions on the release of growth factors in platelet-rich blood derivatives

Abstract: Thrombocytes can be concentrated in blood derivatives and used as autologous transplants e.g. for wound treatment due to the release of growth factors such as platelet derived growth factor (PDGF). Conditions for processing and storage of these platelet-rich blood derivatives influence the release of PDGF from the platelet-bound α-granules into the plasma. In this study Platelet rich plasma (PRP) and Platelet concentrate (PC) were produced with a fully automated centrifugation system. Storage of PRP and PC for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…2,10 Among many growth factors, PDGF-BB is one of the most important in the regeneration and healing of wounds or damaged tissue. 9,10 PDGF-BB levels in the three groups showed no significant difference. The interesting fact from this study is that the mean of platelet counts found in such platelet rich plasma products was not directly proportional to the levels of PDGF-BB after platelet activation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…2,10 Among many growth factors, PDGF-BB is one of the most important in the regeneration and healing of wounds or damaged tissue. 9,10 PDGF-BB levels in the three groups showed no significant difference. The interesting fact from this study is that the mean of platelet counts found in such platelet rich plasma products was not directly proportional to the levels of PDGF-BB after platelet activation.…”
Section: Discussionmentioning
confidence: 78%
“…8 The benefit of PRP lies in the number of platelets it contains, but more than that can be seen from the level of growth factors released when activated. 9 These growth factors have the highest concentration in platelets and play a very important role in the process of wound healing. 2,10 Among many growth factors, PDGF-BB is one of the most important in the regeneration and healing of wounds or damaged tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of PRP was carried out with a fully automated centrifugation system from 11 ml of whole blood drawn from healthy donors as previously described. 31…”
Section: Methodsmentioning
confidence: 99%
“…Generation of PRP was carried out with a fully automated centrifugation system from 11 ml of whole blood drawn from healthy donors as previously described. 31 Adhesion of thrombocytes. To determine the integrity of the platelets and the ability to release growth factors, the adhesion of thrombocytes onto the printed membrane was tested.…”
Section: Application-oriented Validationmentioning
confidence: 99%